Time: Temperature superposition principle: Application of WLF equation in polymer analysis and composites - Chad Smithson; Marina Stamenović; Maja Nujkić; Slaviša Putić (Zaštita Materijala)
Polymers are the most studied viscoelastic material. The shorter times (high frequencies) corresponding to lower temperatures and long times (low frequencies) to high temperatures. This represents the quantitatively applied time-temperature superposition (TTS). Use of the Williams- Landel-Ferry (WLF) equation and the time-temperature superposition principle enables prediction and modeling of the mechanical and rheological properties of polymeric systems outside the timescale of the experiment. Application and validity of the TTS principle and WLF equation in polymer blends, composites, biopolymers and polymer networks will be discussed in this review.